Regionally distinct regulation of astroglial neurotransmitter receptors by fibroblast growth factor-2 - Reuss, Bernhard; Leung, Doreen Siu Yi; Unsicker, Klaus (Molecular and cellular neuroscience, 2002)
Fibroblast growth factor (FGF)-2 is an abundant astroglial cytokine. We have previously shown that FGF-2 downregulates gap junctions in primary astroglial cultures (B. Reuss et al., 1998, Glia 22, 19-30). We demonstrate now that FGF-2 induces astroglial dopamine (DA) sensitivity and D1 dopamine-receptor (D1DR) antigen and message in cortical and striatal astroglial cultures. On the functional level 10 μmol/L DA triggered transient increases in astroglial [Ca2+]i. In gap-junction-coupled cells, no FGF-2-dependent changes in proportions of DA-responsive cells were observable. However, uncoupling with octanol or 18α-glycirrhetinic acid isolated the smaller population of astrocytes intrinsically sensitive to DA which was significantly increased by FGF-2 in cortical and striatal cultures. Administration of DR-specific substances revealed that FGF-2 upregulated D1DR. These results indicate that downregulation of astroglial gap junctions by FGF-2 is accompanied by an upregulation of D1DR and DA sensitivity, adding a new aspect to the role of FGF-2 in the regulation of brain functions.
Gesehen am 24.11.2016